Implementation of Zuhud Values ​​on Consumerist Attitudes (Analysis Study of Simplicity Values ​​in the Five Souls of Darussalam Gontor Modern Islamic Boarding School) - Laili Fachrul Umam (LECTURES: Journal of Islamic and Education Studies, 2026)
The purpose of this article is to discuss the concept of Five Spirits a in Sufism, focusing on the value of simplicity to answer the consumptive problems of modern society. The type of research used in this study is qualitative-descriptive research using philosophical and deductive approaches to manage the data. The results showed that the concept of zuhud in simplicity, as the third pillar of Five Spirits, can overcome the challenges of modernity and consumerism. Based on indicators of fundamental and fundamental concepts contained in Simplicity of Five Spirits. Where the research shows that the application of the Five Spirits concept can be a valuable guide in dealing with the complexities of modern society, forming wise consumptive behavior in accordance with religious values